2005
DOI: 10.1021/jm0493109
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Substituted α-Alkyl Phenethylamines as Selective and Reversible MAO-A Inhibitors:  Biological Activities, CoMFA Analysis, and Active Site Modeling

Abstract: A series of phenethylamine derivatives with various ring substituents and with or without N-methyl and/or C-alpha methyl or ethyl groups was synthesized and assayed for their ability reversibly to inhibit monoamine oxidase A (MAO-A) and monoamine oxidase B (MAO-B). Several compounds showed potent and selective MAO-A inhibitory activity (IC(50) in the submicromolar range) but none showed appreciable activity toward MAO-B. A three-dimensional quantitative structure-activity relationship study for MAO-A inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 31 publications
(78 reference statements)
0
46
0
Order By: Relevance
“…9-11 Structure-activity relationship (SAR) studies, including quantitative analyses (QSAR), [10][11][12] have shown that the presence of electron-donating, unbranched, alkylthio substituents at the para position of the aromatic ring of the amphetamine scaffold generate potent and selective MAO-A inhibitors. In addition, a few studies have shown that the (S)-isomers of substituted amphetamines (which are always dextrorotatory) are the eutomers.…”
Section: Introductionmentioning
confidence: 99%
“…9-11 Structure-activity relationship (SAR) studies, including quantitative analyses (QSAR), [10][11][12] have shown that the presence of electron-donating, unbranched, alkylthio substituents at the para position of the aromatic ring of the amphetamine scaffold generate potent and selective MAO-A inhibitors. In addition, a few studies have shown that the (S)-isomers of substituted amphetamines (which are always dextrorotatory) are the eutomers.…”
Section: Introductionmentioning
confidence: 99%
“…The 1 H NMR spectrum has been reported for the α-methyl homologue 4 of 2C-T in D2O, [48] and for the α-methyl, α-ethyl, and N-methyl homologues of the 2C-T series (and the Ψ-2C-T series 5 ) in D2O. [71] Trachsel has synthesized additional members of the 2C-T series and has reported their spectra in D2O. [72] 4 ALEPH or DOT: 1-[2,5-dimethoxy-4-(methylsulfanyl)phenyl]propan-2-amine.…”
Section: The 4-rs Family: 4-alkylsulfanyl-25-dimethoxyphenyl Patternmentioning
confidence: 99%
“…4, structure 8) [128]. This scaffold is present in many catecholamine neurotransmitters and small variations in the structure can yield different biogenic amine target inhibitors [98,[129][130][131].…”
Section: Indole and Isatin Analogues-a Series Of Indole And Isatin Anmentioning
confidence: 99%